2015
DOI: 10.1039/c4ra14054k
|View full text |Cite
|
Sign up to set email alerts
|

The enhanced magnetorheological performance of carbonyl iron suspensions using magnetic Fe3O4/ZHS hybrid composite sheets

Abstract: Two-dimensional magnetic Fe 3 O 4 /ZHS hybrid composite sheets were prepared via a two-step microwaveassisted solvothermal synthesis. The successful incorporation of Fe 3 O 4 nanoparticles synthesized in the first step into a zinc hydroxysulfate (ZHS) sheet-like structure formed during the second synthesis step was confirmed by X-ray diffraction, scanning electron microscopy, and vibrating sample magnetometry. The obtained magnetic Fe 3 O 4 /ZHS hybrid composite particles show a hexagonal and sheet-like morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Thermal decomposition of zinc hydroxide nitrates yields spherical, connected microparticles of ZnO, which go on to form long chains and two-dimensional networks of polyhedral to rounded nanoparticles, as seen in Figure 2 e,h. The ZnO phase obtain this morphology during annealing as a legacy of original layered morphology of zinc hydroxide nitrates by topotactic transition [ 25 , 45 ]. The diameters of the ZnO nanoparticles range up to 100 nm in size.…”
Section: Resultsmentioning
confidence: 99%
“…Thermal decomposition of zinc hydroxide nitrates yields spherical, connected microparticles of ZnO, which go on to form long chains and two-dimensional networks of polyhedral to rounded nanoparticles, as seen in Figure 2 e,h. The ZnO phase obtain this morphology during annealing as a legacy of original layered morphology of zinc hydroxide nitrates by topotactic transition [ 25 , 45 ]. The diameters of the ZnO nanoparticles range up to 100 nm in size.…”
Section: Resultsmentioning
confidence: 99%
“…Jiang et al [19] employed Fe nanowires into the conventional carbonyl iron particles (CIPs) based MR fluids to prepare dimorphic MR fluids and got a greatly enhanced dynamic yield stress. In addition, Piao et al [20] and Machovsky et al [21] were reported separately that the addition of polyaniline/Fe composite nanofiber and Fe 3 O 4 /ZHS hybrid composite sheets into the CI based MR suspensions results in a significant increase in MR performance. Inspired by these methods, this study aims to extend the dimorphic systems to the MRGs research for improving the rheological properties.…”
Section: Introductionmentioning
confidence: 97%
“…magnetic nanofibers, nanowires and nanosheets) have been studied in the MR literature in the past. These experiments determined that dimorphic MR materials exhibit improved rheological properties and better stability [17][18][19][20][21]. Li et al [17] fabricated and tested a series of bimodal particle MRE samples with different particle sizes of 50 and 5 μm.…”
Section: Introductionmentioning
confidence: 97%
“…In view of the work by Foister (1997), most of the following literature in this field concerned non-Brownian suspensions with σ S ≈ 1 μm and, therefore, σ L /σ S ≈ 10. Most of these works provided similar observations to Foister (1997) with bimodal suspensions giving place to larger yield stresses than monomodal suspensions composed of either the small or the large particles. Although the observed off-state viscosity reduction is well understood in terms of particle packing characteristics, the on-state yield stress enhancement is still not well understood. Bearing in mind that the effect of relative particle sizes on the magnetostatic force magnitude cannot explain the enhancement in the on-state yield stress in bimodal suspensions, one may think that the use of bimodal suspensions would result in more efficiently packed aggregates which are therefore stronger and promote a larger yield stress [e.g., Dodbiba et al (2008)].…”
Section: Introductionmentioning
confidence: 53%